Exploring the impact of thermal energy and exothermic-endothermic reactions on differential type fluid flow in a convergent/divergent channel - Marouan Kouki; Ikram Ullah; Subhan Ullah; Mohammad Mahtab Alam; Hamda Khan; M. Modather M.Abdou (Case Studies in Thermal Engineering, 2024)
This study investigates the thermal energy and reactive processes on nanomaterial flow via convergent/divergent channels. The research looks at how varied channel designs, fluid characteristics, and operating conditions affect flow patterns, temperature distributions, and heat transfer rates. The study focuses on the heat transfer mechanisms within the channels and the effect of exothermic/endothermic reactive processes on fluid flow and temperature profiles. The findings provide vital insights into the behavior of such flow systems, aiding in the comprehension of heat transfer phenomena and prospective applications in engineering domains such as energy systems, chemical processes, and aeronautical engineering.